Theoretical and experimental investigation of thermal and oxidation behaviours of a high speed steel work roll during hot rolling. (October 2017) - Deng, G.Y.; Zhu, H.T.; Tieu, A.K.; Su, L.H.; Reid, M.; Zhang, L.; Wei, P.T.; Zhao, X.; Wang, H.; Zhang, J.; Li, J.T.; Ta, T.D.; et al.
Highlights: Combined theoretical and experimental investigation on thermal and oxidation behaviours of a practical high speed steel work is first reported. Predicted working temperature is used as temperature guidance on high temperature oxidation of HSS work roll materials. Roll surface only undergoes compressive thermal stress when it has an initial roll body temperature less than 100 °C, but tensile stress develops at higher temperature. A compact thin oxide scale develops at roll surface when temperature is higher than 600 °C, but oxidation rate rises fast at temperature higher than 650 °C. Practical oxide scale is more compact than those developed in laboratory due to cyclic mechanical loads. Abstract: In the present study, thermal behaviours of a HSS work roll in actual service condition during hot rolling have been systematically investigated by an experimentally validated model. Influencing factors including finishing stand number, heat transfer coefficients in different circumferential thermal boundaries and initial work roll body temperature have also been carefully examined on the temperature and thermal stress distributions within the work roll. Based on working temperature range at roll surface from the theoretical analysis, oxidation tests of a HSS work roll material have been conducted. It has been observed that the practical HSS oxide scale is obviously different compared to those developed in laboratory not only because of the complicated oxidation atmosphere in industry, but also influenced by the cyclic mechanical load and thermal stress at the work roll surface. Graphical abstract: